Silk-based bilayered small diameter woven vascular conduits for improved mechanical and cellular characteristics. Issue 3 (11th February 2023) - Krishnan, Aarya G.; Joseph, John; C. R., Reshmi; Nair, Shantikumar V.; Nair, Manitha; Menon, Deepthy
Abstract: A major impediment to the development of small diameter vascular grafts is to achieve an optimal balance between its mechanical properties and cellular response. To address this, the technique of cylindrical weaving has been combined with electrospinning to fabricate a seamless bilayered conduit (∼3 mm) having an inner cell-friendly nanofibrous layer of poly(caprolactone)/collagen and an outer mechanically compliant woven silk layer. Mechanical characteristics such as burst strength, suture retention, compliance and leak resistance were found to be improved for this bilayered conduit when compared to the commercial standard. In-vitro studies revealed that the lumen of the conduit was non-hemolytic and could support adhesion and viability of endothelial cells. Overall, our studies suggest that the proposed bilayer construct could be a suitable candidate for small diameter vascular prosthesis. Graphical Abstract: UF0001